DOMAIN ASSESSMENT OF BALI SARDINELLA RESOURCES THROUGH ECOSYSTEM APPROACH AT ARCHIPELAGO FISHING PORT (PPN) PENGAMBENGAN - Rakhma Fitria Larasati; Iya Purnama Sari; Made Mahendra Jaya; Liya Tri Khikmawati; Noar Muda Satyawan; Yulia Estmirar Tanjov; Muth Mainnah; Muh. Arkam Aziz; Noveldesra Suhery; Wulandari Sarasati; Suratna Suratna (Jurnal Teknologi Perikanan dan Kelautan)
Bali sardinella is a fish species that contributes greatly to the Archipelago Fishing Port (PPN) Pengambengan. The potential of Bali sardinella fishery resources is abundant and of high economic value. The purpose of this study was to assess the performance of fish resource domain status with an ecosystem approach. The research was conducted for seven months from January to July 2023. Data collection was done through observation and interviews. The data analysis used was a multi-criteria analysis approach with assessment and visualization of the composite index with a flag model. Six indicators in the fish resources (SDI) domain were studied, namely standardized CPUE trends, Bali sardinella size, proportion of juveniles caught, species composition of the catch, range collapse of fish resources, and endangered, threatened, and protected species (ETP). Indicators in the fish resources domain indicate that the trend of standardized CPUE is decreasing, the trend of Bali sardinella size is relatively fixed, the proportion of juveniles caught is 53%, the species composition of the catch is a higher proportion of target fish, the range collapse of fish resources for fishing grounds is relatively fixed depending on the target species, and for ETP species caught but released. The final result of the assessment of the status of Bali sardinella fish resources based at PPN Pengambengan received a composite score of 70, so it is in a good category.